Modeling Coral Bleaching Mitigation Potential of Water Vertical Translocation – An Analogue to Geoengineered Artificial Upwelling - Feng, Ellias Y.; Sawall, Yvonne; Wall, Marlene; Lebrato, Mario; Fu, Yao (Frontiers in Marine Science, 2020)
Artificial upwelling (AU) is a novel geoengineering technology that brings seawater from the deep ocean to the surface. Within the context of global warming, AU techniques are proposed to reduce sea surface temperature at times of thermal stress around coral reefs. A computationally fast but coarse 3D Earth System model (3.6° longitude × 1.8° latitude) was used to investigate the environmental impacts of hypothetically implemented AU strategies in the Great Barrier Reef, South China Sea, and Hawaiian regions. While omitting the discussion on sub-grid hydrology, we simulated in our model a water translocation from either 130 or 550 m depth to sea surface at rates of 1 or 50 m3 s−1 as analogues to AU implementation. Under the Representative Concentration Pathway 8.5 emissions scenario from year 2020 on, the model predicted a prevention of coral bleaching until the year 2099 when AU was implemented, except under the least intense AU scenario (water from 130 m depth at 1 m3 s−1). Yet, intense AU implementation (water from 550 m depth at 50 m3 s-1) will likely have adverse effects on coral reefs by overcooling the surface water, altering salinity, decreasing calcium carbonate saturation, and considerably increasing nutrient levels. Our result suggests that if we utilize AU for mitigating coral bleaching during heat stress, AU implementation needs to be carefully designed with respect to AU’s location, depth, intensity and duration so that undesirable environmental effects are minimized. Following a proper installation and management procedure, however, AU has the potential to decelerate destructive bleaching events and buy corals more time to adjust to climate change.